Broadcast Media, Mediated Noise, and Discursive Violence - High Decibel TV Debates and the Interrupted Public Sphere - Naveen Mishra (KOME: An International Journal of Pure Communication Inquiry, 2018)
In exploring the role of mediated noise in socio-political discourse, this paper discusses how noise as an element of the communication model with interruption as its fixed meaning needs reconsideration. Against the backdrop of criticism by the media critics and analysts about high decibel debates in broadcast media, this paper critically analyses the centrality of mediated noise in the political and public discourse in India. Noise, it argues, has emerged as a political device and a discursive weapon employed by the dominant stakeholders, capable of steering discourse and manipulating the public opinion that diverts attention from the pressing issues and emphasizes the political wrangling between the stakeholders while disrupting the discursive process. It underscores how dominant groups produce, manage, and mediate noise as a part of their discursive strategy that simulates constructed sincerity and its unquestionable existence. It is shown that meticulously crafted and stage-managed debate panels in broadcast media are aimed at creating a visual spectacle and are driven by commercial and political interests rather than the concern for informed discourse and debate. Noise, in this sense, is a sound that persuasively refers to its significance, as it creates a realm of discursive ambiguity and undermines a discursive process and its subsequent knowledge. Thus, noise is argued to be a form of discursive violence that manifests in the form of voices that distort the facts, dismiss, or deride a narrative, suppress opposing viewpoints, negate the possibility of discussion, and sabotage opportunities for discourse by creating an atmosphere of fear and violence.